Tobacco Budworm, Heliothis virescens (Fabricius) (Insecta: Lepidoptera: Noctuidae) - John L. Capinera (EDIS)
This document is EENY-219, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: July 2001.